2019
DOI: 10.2196/13939
|View full text |Cite
|
Sign up to set email alerts
|

An Intergenerational Information and Communications Technology Learning Project to Improve Digital Skills: User Satisfaction Evaluation

Abstract: Background “Digital Partners” is an intergenerational information and communications technology learning project carried out in the municipalities of Vic and Centelles (Catalonia) from April to May 2018. Within the framework of the introduction of community service as a subject in secondary education, the Centre for Health and Social Studies (University of Vic) created a training space with 38 intergenerational partners (aged 14-15 years and >65 years), with the aim of improving the senior users… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 46 publications
0
10
0
1
Order By: Relevance
“…Because skills seem to be crucial for older people to benefit from online services, training should be provided for them [ 29 ]. A study found that older people were satisfied with ICT training that included working in couples, practicing with the device, choosing what to learn, and practicing material that facilitates communication and learning [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Because skills seem to be crucial for older people to benefit from online services, training should be provided for them [ 29 ]. A study found that older people were satisfied with ICT training that included working in couples, practicing with the device, choosing what to learn, and practicing material that facilitates communication and learning [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Skills can be improved by ICT training that includes working in pairs, device training, the possibility to influence what is taught and material that enables communication and learning (Lopez Segui et al, 2019). The health and social service providers as well as non-governmental organizations should consider ways to improve health literacy among vulnerable groups as this is likely to have an effect on attitudes towards using digital services for health benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The intergenerational programs can enhance cooperation and collaboration and involvement in activities that were related to real life. In other words, in our interventions, teamwork was an opportunity to focus on social interaction of older adults and PwD (LópezSeguí et al, 2019). According to Teater (2016), intergenerational interventions are reported as one type of social activity that may promote active aging among old people.…”
Section: Discussionmentioning
confidence: 99%